2016
DOI: 10.9767/bcrec.11.1.415.48-58
|View full text |Cite
|
Sign up to set email alerts
|

Kinetics and Thermodynamics of Ultrasound-Assisted Depolymerization of κ-Carrageenan

Abstract: The ultrasound-assisted depolymerization of κ-carrageenan has been studied at various temperatures and times. The κ-carrageenan with initial molecular weight of 545 kDa was dispersed in water to form a 5 g/L solution, which was then depolymerized in an ultrasound device at various temperatures and times. The viscosity of the solution was measured using Brookfield viscometer, which was then used to find the number-average molecular weight by Mark-Houwink equation. To obtain the kinetics of κcarrageenan depolyme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
38
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(42 citation statements)
references
References 50 publications
(95 reference statements)
3
38
1
Order By: Relevance
“…K-carrageenan can be depolymerized using various techniques, such as thermal depolymerization [6], acid-catalyzed hydrolysis [7][8][9][10][11], enzymatic hydrolysis [2], ozone oxidation [12], and ultrasound irradiation [13]. When a polysaccharide solution is subjected to an ultrasound irradiation, the ultrasound wave will cause a cavitation which consists of the nucleation, growth, and collapse of microbubbles.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…K-carrageenan can be depolymerized using various techniques, such as thermal depolymerization [6], acid-catalyzed hydrolysis [7][8][9][10][11], enzymatic hydrolysis [2], ozone oxidation [12], and ultrasound irradiation [13]. When a polysaccharide solution is subjected to an ultrasound irradiation, the ultrasound wave will cause a cavitation which consists of the nucleation, growth, and collapse of microbubbles.…”
Section: Introductionmentioning
confidence: 99%
“…Ratnawati et al [13] investigated the effect of temperature on the thermodynamics and kinetics of depolymerization of -carrageenan at pH 9 with the assistance of ultrasound irradiation. There has been no researcher concerned on the effect of pH on the ultrasound-assisted of hydrolysis of k-carrageenan.…”
Section: Introductionmentioning
confidence: 99%
“…In this work, the rate constant for second order model (ks) at pH 10 is 7.21×10 -5 min -1 . Ratnawati et al [29] who degraded κ-carrageenan by ultrasound method found that the kinetics rate constant for pseudo-first order model at 30 o C and pH 10 was 1.74×10 -6 min -1 . The rate constant of ozone treatment is 41.4 fold of that of ultrasonic treatment.…”
Section: Kinetics Depolymerization Of κ-Carrageenan By Ozone Treatmentmentioning
confidence: 99%
“…There were several different techniques, such as microwave-assisted depolymerization [28], sonication [29][30][31], irradiation [17,32], and oxidation using H2O2 [21,33]. Acidic hydrolysis has been considered as a common and fast method to produce a series of carrageenan oligomers, but the use of chemicals causes a potential increase in the level of environmental pollution.…”
Section: Introductionmentioning
confidence: 99%
“…Next article in this issue is about kinetics and thermodynamics of ultrasound-assisted depolymerization of κ-carrageenan by Ratnawati et al [7]. They found that the results were compared to the result of thermal depolymerization by calculating the half life.…”
mentioning
confidence: 99%